2020
DOI: 10.3389/fmicb.2020.536932
|View full text |Cite
|
Sign up to set email alerts
|

Hatching of Globodera pallida Induced by Root Exudates Is Not Influenced by Soil Microbiota Composition

Abstract: Plant-parasitic nematodes are among the most harmful pests of cultivated crops causing important economic losses. The ban of chemical nematicides requires the development of alternative agroecological approaches to protect crops against nematodes. For cyst nematodes, egg hatching is stimulated by host plant root exudates. Inducing “suicide hatching” of nematode second-stage juveniles (J2), using root exudates in the absence of the host plant, may constitute an effective and innovative biocontrol method to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Moreover, unlike with the use of chemical treatments, no toxic residues remain in the soils. The unwanted effects on soil structure, as observed in steamed or autoclaved soils, are completely missing and the dynamics of the loss or unavailability of major nutrients might not be affected; even high doses of γ irradiation at 35 kGy do not affect the physicochemical properties of the treated soils [43]. Our findings also reflect that the maize seedling growth in irradiated soils was similar to the growth in untreated soils.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, unlike with the use of chemical treatments, no toxic residues remain in the soils. The unwanted effects on soil structure, as observed in steamed or autoclaved soils, are completely missing and the dynamics of the loss or unavailability of major nutrients might not be affected; even high doses of γ irradiation at 35 kGy do not affect the physicochemical properties of the treated soils [43]. Our findings also reflect that the maize seedling growth in irradiated soils was similar to the growth in untreated soils.…”
Section: Discussionsupporting
confidence: 52%
“…In recent years, studies have revealed VOCs emitted by plant residues with nematicidal activity similar to commercial nematicides (Gomes et al, 2020;. In the present study, several compounds identified in plant emissions, such as 3-methyl-1-butanol, 2-methyl-1-butanol, 3-pentanone, 2-nonanone, linalool, m-cymene, 2-octanol, 2-ethyl-1hexanol, ethyl acetate, 2-ethylfuran and 2-octanone JOURNAL OF NEMATOLOGY have proven nema ticidal activity (Aissani et al, 2015;Gu et al, 2007;Hewavitharana et al, 2014;Sharma et al, 2018;Zhai et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…VOCs were extracted via headspace solid phase microextraction (SPME) (Arthur and Pawliszyn, 1990). The parameters for SPME and gas chromatography-mass spectrometry (GC-MS) were identical to those described in previous work by Gomes et al (2020).…”
Section: Characterization Of the Vocs Emitted By Soybeans Beans Ryegrass And Alfalfamentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat-root associated microbial community assembly was shaped predominantly by different factors while within each factor, location had stronger effects on the variation in prokaryotic community than growth stage or variety. Similarly, crops affect the soil microbial community and nutrients in the farmland ecosystem (Gautier et al, 2020). Simultaneously, microbial substrate decomposition, energy transfer, and nutrient cycling adversely affect crop development (Stefan et al, 2021;Xie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%